Ferramentas CAD/CAM e a arquitectura Digital - Tiago Vieira de Castro Alves (2013)
Technological developments over the centuries lived definitely marks the role of the architect in society. The great revolutions in technology allow you to achieve new levels of creative freedom and creating new paradigms only possible to understand at the time they are inserted. With the digital age, the potential generator of creative digital tools, together with previous advances in aerospace, marine and automotive, allowed to discover new dimensions of architectural design and develop a more sophisticated construction. These tools are also seen as mechanisms for converting digital models in real scale architectural artifacts, and the project developed on the computer results directly in its material realization, completely changing the methodology of architectural activity. The manufacturing process through the CAD / CAM systems depends on three steps: first, the use of software that let you explore the idea of the project, and secondly, to obtain a digital model that allows the project to convert a set of instructions, to, thirdly, the machinery manufacturing CAM interpret and implement the object. A wellbuilt model is a functional and informative tool, which is intended to review and make all the decisions before construction phase starts. By observing the work of some contemporary architects, can be considered that the introduction of digital tools allowed the reinvention of tectonics in shaping the architectural object, by allowing the exploration of form and greater attention to detail. However, contrary to what is normal in the history of architecture, it is not possible to associate a specific language to this moment, making it difficult to take it like a chain. Anyway, it is undisputed that the methodological change the landscape began what we call digital architecture.